(untitled) (Jurnal Destinasi Pariwisata, 2025)
Along with the development of tourism, seaweed cultivation in Nusa Penida is slowly starting to fade. Seaweed cultivation in Semaya Hamlet holds great potential to be developed as an agro-tourism attraction. This study aims to identify the potential, supporting and inhibiting factors, and development strategies for seaweed agro-tourism in Semaya Hamlet. This research used a descriptive qualitative approach with data collection techniques through observation, interviews, and document studies. Data were analysed using IFAS, EFAS, IE matrix, and SWOT analysis to formulate strategies. The results showed that seaweed farming has appeal from educational, economic, and environmental aspects. The main strengths include community involvement and strategic location, while the weaknesses are limited facilities and human resource capacity. Opportunities arise from nature tourism trends and local government support. Major threats include price fluctuations and pressure on the environment and coastal space. The strategy set is in quadrant V, namely hold and maintain with an emphasis on market penetration and product development. This research concluded that seaweed agro-tourism in Semaya Hamlet has the potential to be developed sustainably through collaboration between the community, government, and business actors.